Microbial degradation and transformation of PPCPs in aquatic environment: A review - Mathiyazhagan Narayanan; Sabariswaran Kandasamy; Jintae Lee; Selvaraj Barathi (Heliyon, 2023)
The Pharmaceuticals and Personal Care Products (PPCPs) presence at harmful levels has been identified in aquatic ecosystems all over the world. Currently, PPCPs are more common in aquatic regions and have been discovered to be extremely harmful to aquatic creatures. Waste-water treatment facilities are the primary cause of PPCPs pollution in aquatic systems due to their limited treatment as well as the following the release of PPCPs. The degree of PPCPs elimination is primarily determined by the method applied for the remediation. It must be addressed in an eco-friendly manner in order to significantly improve the environmental quality or, at the very least, to prevent the spread as well as effects of toxic pollutants. However, when compared to other methods, environmentally friendly strategies (biological methods) are less expensive and require less energy. Most biological methods under aerobic conditions have been shown to degrade PPCPs effectively. Furthermore, the scientific literature indicates that with the exception of a few extremely hydrophobic substances, biological degradation by microbes is the primary process for the majority of PPCPs compounds. Hence, this review discusses about the optimistic role of microbe concerned in the degradation or transformation of PPCPs into non/less toxic form in the polluted environment. Accordingly, more number of microbial strains has been implicated in the biodegradation/transformation of harmful PPCPs through a process termed as bioremediation and their limitations.